Extensive curettage using a high-speed burr versus dehydrated alcohol instillation for the treatment of enchondroma of the hand. (May 2015) - Cha, S. M.; Shin, H. D.; Kim, K. C.; Park, I. Y.
The purpose of this retrospective study was to compare the clinical and radiological outcomes of patients treated with different adjuvant methods after curettage for enchondromas of the hand. Sixty-two patients with enchondroma were treated with high-speed burring (29 patients) or alcohol instillation (33 patients) after curettage. The mean follow-up was 40.8 months. No significant differences in the visual analogue scale, Disabilities of the Arm, Shoulder, and Hand scores, total range of active motion, grip strength, and complete healing time were observed between the groups. The distribution of the results of the formula by Wilhelm and Feldmeier were not significantly different between the groups. No surgery-related complications, postoperative pathological fractures, or recurrence was found in either group. For the treatment of enchondroma in the metacarpal and proximal phalanx, alcohol instillation immediately after curettage was as effective as extensive curettage using a high-speed burr.